Meckel's diverticulum perforation in a newborn positive to Sars-Cov-2 - E. Bindi; A. Cruccetti; M. Ilari; F. Mariscoli; V.P. Carnielli; A. Simonini; G. Cobellis (Elsevier, 2020)
The health emergency linked to the Sars-Cov-2 infection represented an absolutely new problem for all health professionals. In particular, the information regarding the spread of the virus in the pediatric field and its manifestations are still incomplete. In this paper we present a case of neonatal infection which, as far as we know, represents one of the few published cases and which occurred in a patient who came to our attention for acute abdomen from intestinal perforation. The perforation was caused by Meckel's diverticulum, an event considered infrequent in the first year of life and almost exceptional in the neonatal period. This case required particular management, putting pediatric surgeons in front of new and difficult to solve problems. New onset clinical events, such as this one described, represent an opportunity for sharing useful data for the creation of universal protocols for the management of patients with problems that are becoming common and of which little is known.